Molecular Characterization of Actinomyhcin D Producing Streptomyces Strain Isolated from Soil Samples (Bangladesh Pharmaceutical Journal, 2012)
The taxonomic position of an actinomycete strain, MARS-17 has been examined in this present study. Based on the morphological, biochemical and cultural characteristics, the strain was identified as a species of genus Streptomyces. It formed light brownish gray aerial mycelia and produced yellow-colored diffusible pigments. The 16S rRNA gene of this strain was sequenced and phylogenetic analysis using the sequence showed that the strain is most closely related to Streptomyces parvulus AB184326 (99.6%) and Streptomyces malachitospinus AB249954 (99.0%). On the basis of the 16S rDNA sequence and phenotypic characteristics, the strain was identified as a new type strain of Streptomyces parvulus. The strain produced a single antimicrobial compound in the Czapek-dox fermentation media which was indentified as actinomycin D from its spectral data. DOI: http://dx.doi.org/10.3329/bpj.v15i2.12574 Bangladesh Pharmaceutical Journal 15(2): 113-117, 2012